Breve noticia de la enseñanza de lenguas extranjeras: nuevas tecnologías y bilingüismo en una Comunidad Autónoma - Ardila, J.A.G. (Revista Complutense de Educación, 2006)
Educationalists in Spain have envisaged a drastic changed in foreign language teaching, to be brought about in the forthcoming future. Indeed it is expected that foreign language teaching will soon begin in early childhood, rely on electronic resources, and take place in bilingual schools. These three actions have been taken in Extremadura since the 90s - Extremadura being the first Spanish region to make English a mandatory subject at all levels of primary education, to provide a PC for every two students in secondary education, and to bring bilingualism to a significant number of publicly-founded schools. This paper seeks to evaluate the results thus far.